Provision of primary care by specialist physicians: a systematic review - Muhammad Jawad Hashim (Family Medicine and Community Health, 2020)
Patients with stable chronic diseases such as diabetes and hypertension can be safely managed at the primary care level. Yet many such patients continue to follow-up with specialists at a higher expense with no added benefit. We introduce a new term to describe this phenomenon: scope inversion, defined as the provision of primary care by specialist physicians. We aimed to quantify the extent of scope inversion by conducting a systematic review. MEDLINE and five other databases were searched using the keywords ‘specialist AND (routine OR primary) AND provi*’ as well as other variations. The search was limited to human research without restrictions on language or date of publication. The inclusion criterion was studies on rates of the provision of routine primary care by specialist physicians. Thirteen observational studies met the inclusion criteria. A wide range of primary care involvement was observed among specialists, from 2.6% to 65% of clinic visits. Among children, 41.3% of visits with specialists were routine follow-ups for conditions such as allergic rhinitis and seborrhoeic dermatitis which could be managed in primary care. Data quality was moderate to low across the studies due to limitations of source data and varying definitions of primary care. Specialist physicians provide primary care to patients in a substantial proportion of clinic visits. Scope inversion is wasteful as it diverts patients to more expensive care without improving outcomes. A systems approach is needed to mitigate scope inversion and its harmful effects on healthcare service delivery.